The Car Chase as Allegory for the Loss of the American Dream: The Case of Dirty Mary, Crazy Larry - Scott Pearce ([sic])
This paper focuses on the John Hough film Dirty Mary, Crazy Larry (1974). Using the work of Sabina Spielrein, this paper situates the car chase in the film as allegorical and as representing a desire for economic and social rebirth for its titular characters. However, the economic, political, and social upheaval of the period means that such desire is impossible to fulfill. Contextually, the promise of systemic change, so potent in 1960s America, had not fully materialized. The car chase that makes up much of the film then becomes a death drive for the characters. This positions the titular characters as variations on the absurd hero that Albert Camus articulates in The Myth of Sisyphus. They flee from institutional authority with little hope of escape, yet they flee anyway, finding meaning in the rebellion. Dirty Mary, Crazy Larry differs thematically from the car chase films of the late 1970s and early 1980s. These later incarnations reappropriated the car chase to mute the genre’s capacity to provide a critique of dominant social and political discourses. Dirty Mary, Crazy Larry is underrepresented in critical writing, and this paper seeks to redress this underrepresentation.